Reduced Structural Connectivity in Frontostriatal White Matter Tracts in the Associative Loop in Schizophrenia - Levitt, James J; Nestor, Paul G; Levin, Laura; Pelavin, Paula; Lin, Pan; Kubicki, Marek; McCarley, Robert W; Shenton, Martha E; Rathi, Yogesh (The American journal of psychiatry, 2017)
Objective:The striatum receives segregated and integrative white matter tracts from the cortex facilitating information processing in the cortico-basal ganglia network. The authors examined both types of input tracts in the striatal associative loop in chronic schizophrenia patients and healthy control subjects.Method:Structural and diffusion MRI scans were acquired on a 3-T system from 26 chronic schizophrenia patients and 26 matched healthy control subjects. Using FreeSurfer, the associative cortex was parcellated into ventrolateral prefrontal cortex and dorsolateral prefrontal cortex subregions. The striatum was manually parcellated into its associative and sensorimotor functional subregions. Fractional anisotropy and normalized streamlines, an estimate of fiber counts, were assessed in four frontostriatal tracts (dorsolateral prefrontal cortex-associative striatum, dorsolateral prefrontal cortex-sensorimotor striatum, ventrolateral prefrontal cortex-associative striatum, and ventrolateral prefrontal cortex-sensorimotor striatum). Furthermore, these measures were correlated with a measure of cognitive control, the Trail-Making Test, Part B.Results:Results showed reduced fractional anisotropy and fewer streamlines in chronic schizophrenia patients for all four tracts, both segregated and integrative. Post hoc t tests showed reduced fractional anisotropy in the left ventrolateral prefrontal cortex-associative striatum and left ventrolateral prefrontal cortex-sensorimotor striatum and fewer normalized streamlines in the right dorsolateral prefrontal cortex-sensorimotor striatum and in the left and right ventrolateral prefrontal cortex-sensorimotor striatum in chronic schizophrenia patients. Furthermore, normalized streamlines in the right dorsolateral prefrontal cortex-sensorimotor striatum negatively correlated with Trail-Making Test, Part B, time spent in healthy control subjects but not in chronic schizophrenia patients.Conclusions:These findings demonstrated that structural connectivity is reduced in both segregated and integrative tracts in the striatal associative loop in chronic schizophrenia and that reduced normalized streamlines in the right-hemisphere dorsolateral prefrontal cortex-sensorimotor striatum predicted worse cognitive control in healthy control subjects but not in chronic schizophrenia patients, suggesting a loss of a “normal” brain-behavior correlation in chronic schizophrenia.